Existence and stability results for nonlinear coupled singular fractional-order differential equations with time delay - Hasanen A. Hammad; Hüseyin Işık; Manuel De la Sen (AIMS Mathematics, 2023)
The objective of the manuscript is to build coupled singular fractional-order differential equations with time delay. To study the underline problem, an integral representation is initially discussed and the operator form of the solution is investigated using various supplementary hypotheses. Also, the existence and uniqueness of the considered problem are investigated by using the Lebesgue-dominated convergence theorem and some analysis results. Moreover, the stability analysis to determine the nature of the proposed model's solution is examined. Finally, two supportive examples are provided to demonstrate our analysis as applications.